Long Term Optimal DG Placement Considering Transmission System Reliability and Load Uncertainty - Ali Badri; Mahdy Norouzi (Majlesi Journal of Electrical Engineering)
DG (dispersed generation) application has received increasing attention during recent years. The impact of DG on various aspects of distribution system characteristics depends highly on DG location in distribution feeder. This paper presents an optimization method to determine long term optimal DG placement in distribution systems in which system reliability and operational constraints as well as environmental constraints are taken into account. In order to get more realistic results impact of load uncertainty is modeled using normal distribution function. Furthermore, DG transactions with the market and corresponding payoffs are calculated. Despite, most of studies dealing with the problem from cost minimization point of view in a short term period, here DG placement is investigated from long term perspective. To get more accurate results the model considers both DG benefits and costs and the objective function is based on DG profit maximization. Benefits of using DG consist of loss reduction revenue, reducing in costumers' interruption costs, power purchase saving as well as green house gas and fossil fuel reductions. Whereas, the costs consist of initial costs, maintenance and operating costs and DG transition costs as well. The proposed model is simulated on a standard IEEE test system to obtain the results and show